2014
DOI: 10.1016/j.seizure.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of seizure control in patients with juvenile myoclonic epilepsy (JME)

Abstract: A correct diagnosis of JME does not guarantee an optimal response to therapy. Poorer drug adherence might result in more seizures; this should be highlighted for patients in every single visit. Longer follow-up gives the treating physician more time to adjust the drug(s) and formulate a plan that is appropriate for patients with difficult to treat seizures. We recommend valproate if seizure control is the main objective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 13 publications
0
12
0
2
Order By: Relevance
“…5 However, even for GGE, such a strict correlation has not been formally established thus far 6 and, surprisingly, some authors even suggested that EEG abnormalities may not be valid predictors for seizure recurrence in these syndromes. 7 Among GGE, Juvenile Myoclonic Epilepsy (JME) is quite common; 8 it is characterized by the occurrence of major (generalized tonic clonic-GTC) and minor (myoclonic) motor seizures, with clinical onset in adolescence and young adulthood, and by a significant impact on key aspects of life such as driving, starting a working career and pregnancy. 9 Among GGE, JME is considered to have a peculiar physiopathology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 However, even for GGE, such a strict correlation has not been formally established thus far 6 and, surprisingly, some authors even suggested that EEG abnormalities may not be valid predictors for seizure recurrence in these syndromes. 7 Among GGE, Juvenile Myoclonic Epilepsy (JME) is quite common; 8 it is characterized by the occurrence of major (generalized tonic clonic-GTC) and minor (myoclonic) motor seizures, with clinical onset in adolescence and young adulthood, and by a significant impact on key aspects of life such as driving, starting a working career and pregnancy. 9 Among GGE, JME is considered to have a peculiar physiopathology.…”
Section: Introductionmentioning
confidence: 99%
“…Data obtained in previous studies, 7,11,18 aimed at identifying such potential EEG predictors, were hindered by (1) the intra-/inter-study inhomogeneity of EEG recording lengths, timing, and activation method protocols, (2) the lack of quantitative methods of EEG recordings evaluation and, most importantly, by (3) the fact that EEG recordings are often followed by ASM regimen modification, which can alter the clinical outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…у пациентов с ЮМЭ в исследовании A. Asadi-Pooya. Помимо этого, достаточно сильную связь с ремиссией показало наличие вальпроата в режиме терапии [41].…”
Section: Vol 11 (2)unclassified
“…Обоснованный диагноз ЮМЭ, однако, еще не гарантирует оптимального ответа на терапию. Этот факт нашел свое отражение в работе [18] по иссле-дованию 116 пациентов с ЮМЭ, наблюдаемых по меньшей мере 18 мес каждый. У 68 пациентов за последние 12 мес приступов не было, а у 48 был зарегистрирован хотя бы один приступ разного типа.…”
unclassified